Footstep Power Generation System (International Journal of Engineering and Computer Science, 2017)
Man has used tremendous amount of energy for his daily needs. Therefore large amount of energy has been exhausted and wasted. Footstep power generation system is designed to be very useful at public places like railway stations where lot of people keep walking through all day. In the footstep power generation system the floor sensors capture the electrical energy produced by the pressure and convert it into electrical charge with the help of the piezo transducers which in turn is used as a power source. Thus the piezoelectric technologies is used in flooring. The power source thus generated has a vast amount of applications in home application, agriculture, street lighting and as a energy source for sensors in remote locations